Efeito da terapia fotodinâmica como coadjuvante ao tratamento periodontal não-cirúrgico sobre o quadro periodontal e controle metabólico em pacientes portadores de Diabetes Mellitus tipo 2 - Flavia Isabela Barbosa (2014)
The study aimed to evaluate the effect of antimicrobial photodynamic therapy (aPDT) as an adjunct to non-surgical periodontal treatment (NSPT) on the periodontal status and metabolic control in patients with type 2 diabetes mellitus and chronic periodontitis (moderate / severe). Twelve diabetic patients were included in two randomized treatment groups: 6 patients received NSPT associated with aPDT (G1) and 6 patients received NSPT (G2). The study consisted of five moments, T0, T1, T2, T3 and T4 respectively, patient preparation, treatment, 30, 90, 180 days. In all periods, except T0, reviewed periodontal clinical parameters and serum fructosamine was performed, being held in T1 and T2 collecting gingival crevicular fluid for examination real time PCR (polymerase chain reaction) cytokine and marker of the inflammatory response, and T1, T3 and T4 assay of glycated hemoglobin (HbA1c). The sample consisted of 8 females and 4 males, 5 females in the test and 3 in control group, 1 male patient in the test group and 3 in the control. The average age was 52.17 years and mean duration of diabetes was 9.58 years. Regarding medication use, 67% of patients used oral hypoglycemic agents, insulin 8.3% and 24.7% associated these medications. The groups showed no statistically significant differences when analyzed baseline clinical and metabolic parameters. The Mann Whitney test used for comparison between groups and the Wilcoxon test was used to assess progress within each group in the evaluation periods. The plaque index did not change within each group, but in T2 (30 days) showed that the test group had significantly lower this index the control group (p = 0.02). Regarding the bleeding on probing, both groups showed a significant reduction between T1 and T2 (p = 0.046 and p = 0.04, G1 and G2 respectively), with no difference between groups. In relation to probing depth and clinical attachment level, the groups did not differ from each other, but there was a reduction of the same, which were maintained in all evaluation periods compared to T1. In relation to glycated hemoglobin and fructosamine, there were no significant differences between groups or within the same in any moment. Analysis by real time PCR of mRNA expression levels showed no significant difference in the expression of TNF-, IL-1, MCP-1 and TGF- before and after periodontal treatment but, within 30 days after treatment there was a significant decrease in the IFN- cytokine and cell marker CD4+CD28+ gene expression and increased expression of IL-10. Within the limitations of this study, we can conclude that: a) TPNC, associated or not with aPDT, improves similarly periodontal status in diabetic patients; b) TPNC, associated or not with aPDT not interfere with glycemic control in diabetic and c) TPNC appears to influence the expression of inflammatory cytokines in gingival crevicular fluid of diabetic patients.